Aqueous seeding in intraocular retinoblastoma: A review. (9th July 2021) - Kaliki, Swathi
Abstract: The management of retinoblastoma is complex. With increasing treatment modalities and increasing experience with each treatment modality, the globe salvage rates have drastically improved with time. Aqueous seeding in an eye with retinoblastoma is classified as group E based on International Classification of Intraocular Retinoblastoma, and most group E eyes were enucleated a decade earlier. Newer modalities of treatment have improved the globe salvage rates in group E eyes including those with aqueous seeding. Various globe salvage treatment modalities attempted for the management of aqueous seeds include external beam radiotherapy, plaque radiotherapy, intra‐arterial chemotherapy, periocular chemotherapy, intravitreal chemotherapy and intracameral chemotherapy. Of all treatment modalities, intracameral chemotherapy holds promise for the management of aqueous seeds in selected patients, but it should be done with the utmost care by a trained ocular oncologist. Enucleation is still the preferred modality of treatment for eyes with advanced retinoblastoma and anterior segment invasion. This review focuses on the current evidence on aqueous seeding, highlighting the pathogenesis, classification, clinical presentation, treatment and outcomes.